Analysis Study of Cultural Aspects on Travel to South Korea - Yusila, Anggina; Fatimatuzzahra; Ahmad Nuh (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
People have been impacted by Korean culture due to its global prominence. This Korean culture, sometimes referred to as the Hallyu phenomenon or Korean Wave, encompasses a variety of mediums including fashion, music, theater, makeup, and more. The purpose of this study is to examine how South Korea's cultural phenomena have influenced all generations and contributed to the country's appeal as a travel destination and perhaps inspire plans to travel to South Korea in the near future. The study employed a quantitative methodology and included 116 respondents from the surrounding area. Google Forms is used for online questionnaire delivery. SmartPLS software is used to process the data. We anticipate that the research's findings will give travelers more knowledge about South Korea's attractions, things to do, and other resources so they may make well-informed travel plans. The study's overall conclusions emphasize the significance of perceived advantages and cultural elements in shaping travel intentions to South Korea. The report also emphasizes how important electronic word-of-mouth is in forming traveler perceptions. The ramifications of these findings extend to destination managers and marketers, who may leverage these insights to create customized marketing campaigns that address the interests and needs of prospective guests.